2020
DOI: 10.3390/s20185120
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Apple Varieties Using a Multichannel Hyperspectral Imaging System

Abstract: This paper reports the nondestructive detection of apple varieties using a multichannel hyperspectral imaging system consisting of an illumination fiber and 30 detection fibers arranged at source–detector distances of 1.5–36 mm over the spectral range of 550–1650 nm. Spatially resolved (SR) spectra were obtained for 1500 apples, 500 each of three varieties from the same orchard to avoid environmental and geographical influences. Partial least squares discriminant analysis (PLSDA) models were developed for sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Figure 5 illustrates the mean relative spectra for healthy and early disease blueberries of three spectral preprocessing methods over the spectral range of 400-1000 nm. There were two noticeable absorption peaks for the mean spectra of both healthy and early disease blueberries at around 680 nm, due to chlorophyll, and 970 nm, due to water or O-H functional groups [24,25]. There were no significant differences in the spectral range of 400-685 nm between healthy and early disease fruit, which could be due to the dark color of blueberries, resulting in difficult-to-observe pigment changes.…”
Section: Spectral Features Related To Early Diseasementioning
confidence: 88%
See 1 more Smart Citation
“…Figure 5 illustrates the mean relative spectra for healthy and early disease blueberries of three spectral preprocessing methods over the spectral range of 400-1000 nm. There were two noticeable absorption peaks for the mean spectra of both healthy and early disease blueberries at around 680 nm, due to chlorophyll, and 970 nm, due to water or O-H functional groups [24,25]. There were no significant differences in the spectral range of 400-685 nm between healthy and early disease fruit, which could be due to the dark color of blueberries, resulting in difficult-to-observe pigment changes.…”
Section: Spectral Features Related To Early Diseasementioning
confidence: 88%
“…Hyperspectral imaging, which combines imaging and spectral information to detect external or internal quality attributes, is a promising detection method [20][21][22]. Furthermore, spectral signatures can be used to uniquely characterize, identify and quantify the chemical composition of agricultural products [23][24][25][26], which has advantages in the detection of some early defects that are invisible to the naked eye. In the last decade, numerous studies have been reported on the detection of diseases in fruit using hyperspectral imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the dark reference spectra were acquired by closing the light source in a dark room. The relative spatially resolved spectra for the samples were calculated using the white, the dark and the original sample spectra [ 27 ]. The relative reflectance spectra were used in further data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, HSI has a more comprehensive interpretation for the whole sample, which is conducive in discriminating different geographical origins of agricultural products. In this context, HSI has been widely adopted in the field of agricultural products, including fruits [23], cereals [24][25][26], meats [27], vegetables [28], and seafoods [29]. Additionally, the HSI technique was also often used to screen discolored [30,31], immature [32,33], moldy [34], and insect damage samples [35].…”
Section: Introductionmentioning
confidence: 99%